Perilaku Hidup Bersih dan Sehat (PHBS) Melalui Pendidikan Kesehatan Penggunaan Air Bersih dalam Penurunan Angka Stunting di Desa Cot Beut Kecamatan Kuta Baro Kabupaten Aceh Besar - Hafni Zahara; Erna Safitri; Noeroel Arham; Syukriadi Syukriadi; Urip Pratama; Maheta Sipinteniate; Suci Aulia Nasaputri; Cut Fitri Magfirah; Inda Rahmani (Lembaga Pengembangan Kinerja Dosen, 2025)
Clean and Healthy Living Behavior is a community effort to implement and practice clean and healthy living patterns in order to create a clean and healthy environment that can prevent the spread of disease. The purpose of Clean and Healthy Living Behavior is to increase knowledge, awareness, and progress of the community to live healthily and increase the active role of the community in efforts to realize an optimal standard of living. The benefits of Clean and Healthy Living Behavior are to increase public awareness so that they are willing and able to live a clean and healthy life, can prevent and anticipate health problems that they face. Adequate environmental sanitation is a prerequisite for actively adopting clean and healthy lifestyles. Poor access to clean water and sanitation facilities can increase the incidence of infectious diseases, diverting energy for growth to fight infection, making it difficult for the body to absorb nutrients, and stunting growth. Stunting is a condition of growth failure in children due to prolonged malnutrition and repeated infections, especially in the first 1000 days of life, which is characterized by height that is not appropriate for their age. Health education is the process of conveying information, skills, and understanding about health to the community with the aim of increasing knowledge, awareness, and healthy behavior and motivating individuals to adopt a healthier lifestyle. The community service activity was carried out in Cot Beut Village, Kuta Baro District, Aceh Besar Regency, with 24 participants. This counseling lasted approximately 50 minutes, consisting of material presentation and a question and answer session with participants regarding PHBS. The community was advised to adopt Clean and Healthy Living Behaviors to prevent disease.